2009
DOI: 10.1021/pr900603n
|View full text |Cite
|
Sign up to set email alerts
|

An Initial Characterization of the Serum Phosphoproteome

Abstract: Phosphorylation is a dynamic post-translational protein modification that is the basis of a general mechanism for maintaining and regulating protein structure and function, and of course underpins key cellular processes through signal transduction. In the last several years, many studies of large-scale profiling of phosphoproteins and mapping phosphorylation sites from cultured human cells or tissues by mass spectrometry technique have been published; however, there is little information on general (or global)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 39 publications
5
84
1
Order By: Relevance
“…One member of this family, Fam20C (family with sequence similarity 20, member C), is the physiological casein kinase that phosphorylates multiple secreted proteins within a Ser-x-Glu/pSer motif (7,9,10). The importance of this discovery is underscored by the fact that some 75% of the phosphoproteins identified in human serum and cerebrospinal fluid contain phosphate within this motif (11)(12)(13). Furthermore, mutations in FAM20C cause Raine syndrome, a deadly osteosclerotic bone dysplasia characterized by generalized osteosclerosis, ectopic calcifications, and characteristic facial features (14)(15)(16).…”
mentioning
confidence: 99%
“…One member of this family, Fam20C (family with sequence similarity 20, member C), is the physiological casein kinase that phosphorylates multiple secreted proteins within a Ser-x-Glu/pSer motif (7,9,10). The importance of this discovery is underscored by the fact that some 75% of the phosphoproteins identified in human serum and cerebrospinal fluid contain phosphate within this motif (11)(12)(13). Furthermore, mutations in FAM20C cause Raine syndrome, a deadly osteosclerotic bone dysplasia characterized by generalized osteosclerosis, ectopic calcifications, and characteristic facial features (14)(15)(16).…”
mentioning
confidence: 99%
“…For example, the four most abundant phosphopeptides derived from fibrinogen alpha (T.ADpSGEGDFLAEGGGVR.G, T.ADpSG EGDFLAEGGGV.R, A.DpSGEGDFLAEGGGVR.G, A.DpSGEGDFLA EGGGV.R) are not fully tryptic peptides. They were identified only in this study but not in other proteomic studies [9,10]. CID (MS2 or MSA) is the popular fragmentation method for identifications of phosphopeptides in phosphoproteomic analysis.…”
Section: Discussionmentioning
confidence: 77%
“…Most of the endogenous phosphopeptides identified in this study are not reported in previous proteomic studies using trypsin as digestion enzyme. This is because most of these identified phosphopeptides are partial tryptic or non-tryptic peptides generated by proteases presented in serum [9,10]. For example, the four most abundant phosphopeptides derived from fibrinogen alpha (T.ADpSGEGDFLAEGGGVR.G, T.ADpSG EGDFLAEGGGV.R, A.DpSGEGDFLAEGGGVR.G, A.DpSGEGDFLA EGGGV.R) are not fully tryptic peptides.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations